2021
DOI: 10.1248/cpb.c21-00409
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxyl Radical/Copper-Catalyzed Electrooxidation of Alcohols and Amines at Low Potentials

Abstract: Nitroxyl radicals, such as 2,2,6,6-tetramethylpiperidine N-oxyl (TEMPO), can catalyze the electrochemical oxidation of alcohols and amines. Because the oxidation current obtained in this process depends on the concentration of alcohols and amines, this process can be applied to their sensing. However, the relatively high oxidation potentials required by nitroxyl radicals can induce interfering oxidation currents from various reductive substances in biological samples, which affects the accuracy of analyte meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…95 Kashiwagi has developed enzyme-free electrochemical sensing of alcohol and amine compounds using nitroxyl radical catalysts as organic catalysts (Scheme 24). 96 Furthermore, after the successful tests, the NNO/ copper catalysis can improve the oxidation current at a lower potential; the reactive state is better than that of TEMPO.…”
Section: Nortropine N-oxyl (Nno) As An Effectivementioning
confidence: 99%
“…95 Kashiwagi has developed enzyme-free electrochemical sensing of alcohol and amine compounds using nitroxyl radical catalysts as organic catalysts (Scheme 24). 96 Furthermore, after the successful tests, the NNO/ copper catalysis can improve the oxidation current at a lower potential; the reactive state is better than that of TEMPO.…”
Section: Nortropine N-oxyl (Nno) As An Effectivementioning
confidence: 99%
“…[6][7][8] We have focused on nitroxyl radical compounds, which can work as organocatalysts, to develop electrochemical sensors. [9][10][11][12][13] Nitroxyl radical compounds, such as 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), are used in combination with appropriate oxidants, such as NaClO, to catalyze the oxidation of alcohols in organic synthesis. 14,15) Alcohol can also be oxidized electrochemically by applying an electric potential instead of by oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…We have also developed 3-hydroxy-8-azabicyclo[3.2.1] octane N-oxyl (3-HO-ABOO) (previously named nortropine N-oxyl (NNO), whereas here a more systematic name is used for clarity), and reported electrochemical sensing of glucose and drugs under physiological conditions based on these compounds. [9][10][11][12][13] We reported that 7-azabicyclo[2.2.1] heptan-7-ol (ABHOL), a highly active hydroxylamine catalyst with a new structure, exhibits high catalytic activity for alcohol oxidation under aerobic oxidation conditions using a copper salt as a co-catalyst. 23) ABHOL is oxidized to the corresponding nitroxyl radical (7-azabicyclo[2.2.1] heptane N-oxyl; ABHO) under oxidation reaction conditions and exhibits oxidation catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The development of highly efficient and selective oxidation catalysts is important in several fields, such as organic chemistry, natural product synthesis, and industrial chemistry. Stable nitroxyl radicals have recently attracted considerable attention as metal-free catalysts owing to their safety, environmental sustainability, and designability. Although 2,2,6,6-tetramethylpiperidinyl N -oxyl (TEMPO) is a well-known organic radical catalyst with industrial applications, it is limited to the oxidation of primary alcohols. To overcome this limitation, the stable 2-azaadamantane N -oxyl (AZADO) organic radical was developed as an efficient and selective catalyst for the oxidation of primary and secondary alcohols under mild conditions. The difference in the catalytic activity of AZADO and TEMPO was explained as a steric effect arising from the existing bulky substitution of four methyl groups at the 2- and 6-positions. Although numerous AZADO derivatives (Scheme ) have been synthesized and applied to AZADO-mediated catalytic oxidation, explaining their reactivity purely in terms of steric effects is challenging.…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 To overcome this limitation, the stable 2-azaadamantane N -oxyl (AZADO) organic radical was developed as an efficient and selective catalyst for the oxidation of primary and secondary alcohols under mild conditions. 7 12 The difference in the catalytic activity of AZADO and TEMPO was explained as a steric effect arising from the existing bulky substitution of four methyl groups at the 2- and 6-positions. Although numerous AZADO derivatives ( Scheme 1 ) have been synthesized and applied to AZADO-mediated catalytic oxidation, explaining their reactivity purely in terms of steric effects is challenging.…”
Section: Introductionmentioning
confidence: 99%